1991
DOI: 10.1111/j.1540-8159.1991.tb02884.x
|View full text |Cite
|
Sign up to set email alerts
|

Tachycardia Recognition and Diagnosis from Changes in Right Atrial Pressure Waveform—A Feasibility Study

Abstract: Implantable defibrillators either monitor heart rate or use a probability density function to detect ventricular fibrillation/tachycardia. As a result, they are unable to discriminate sinus tachycardia and atrial arrhythmias from malignant ventricular rhythms. We have assessed high fidelity fiber-optic pressure recordings in the right atrium during cardiac arrhythmias in 23 patients (mean age 44 years, 11 females) undergoing electrophysiological study. The unfiltered pressure signal was amplified and recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…While Gùrsoy et al 3 . observed lower RAP and less flow reversal in the vena cava during atrial systole (assessed by angiography) during native AVRT than during native AVNRT, other studies failed to find a significant difference, in terms of right 13 and left atrial pressures (PCWP) 14 . The location of the bypass tract may affect the hemodynamics during AVRT.…”
Section: Discussionmentioning
confidence: 99%
“…While Gùrsoy et al 3 . observed lower RAP and less flow reversal in the vena cava during atrial systole (assessed by angiography) during native AVRT than during native AVNRT, other studies failed to find a significant difference, in terms of right 13 and left atrial pressures (PCWP) 14 . The location of the bypass tract may affect the hemodynamics during AVRT.…”
Section: Discussionmentioning
confidence: 99%
“…Right atrial pressure generally increases in the context of a rapid tachyarrhythmia regardless of its underlying nature. 8 In patients with a patent foramen ovale or an ASD with a predominant left-to-right shunt at rest, the tachycardia-induced increase in right atrial pressure can result in shunt reversal with hypoxemia and symptoms of HF. The classic example is the patient with Ebstein anomaly and exertional or tachycardia-induced oxygen desaturation.…”
Section: Hypoxemiamentioning
confidence: 99%
“…High fidelity pressure recordings clearly demonstrate the relation between atrial and ventricular contraction and characteristic patterns have been demonstrated associated with specific atrial and ventricular arrhythmias.65 Mean right atrial pressure showed an increase during all types of arrhythmia, regardless of haemodynamic stability, with a considerable degree of overlap between atrial and ventricular arrhythmias, though there was a preponderance of well tolerated arrhythmias in the study. 66 Development of a pattern-recognition algorithm and a reliable high fidelity chronic pressure sensing catheter may allow atrial pressure waveforms to become a realistic method for tachycardia diagnosis.…”
Section: Right Ventricular Pressure Measurementmentioning
confidence: 99%